2012
DOI: 10.3390/v4010001
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Humoral Innate Immunity in Hepatitis C Virus Infection

Abstract: Infection with Hepatitis C Virus (HCV) causes chronic disease in approximately 80% of cases, resulting in chronic inflammation and cirrhosis. Current treatments are not completely effective, and a vaccine has yet to be developed. Spontaneous resolution of infection is associated with effective host adaptive immunity to HCV, including production of both HCV-specific T cells and neutralizing antibodies. However, the supporting role of soluble innate factors in protection against HCV is less well understood. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 175 publications
(198 reference statements)
1
33
1
Order By: Relevance
“…The recognition of both native and recombinant IHNV-G protein by the antisera from G-C5a immunized trout strongly suggests that the G portion of the recombinantly produced G-C5a protein maintains conformational epitopes important for the antigenicity of native IHNV-G protein. The C5a's roles involve the recruiting of APCs, facilitation of antigen uptake by the innate and adaptive immune receptors on APCs, and enhancement of antigen-specific antibody responses in mammals [37,38]. Our results indicate that fusing trout C5a to G protein in the recombinant protein vaccine increased both the kinetics and longevity of the antibody response.…”
Section: Discussionmentioning
confidence: 73%
“…The recognition of both native and recombinant IHNV-G protein by the antisera from G-C5a immunized trout strongly suggests that the G portion of the recombinantly produced G-C5a protein maintains conformational epitopes important for the antigenicity of native IHNV-G protein. The C5a's roles involve the recruiting of APCs, facilitation of antigen uptake by the innate and adaptive immune receptors on APCs, and enhancement of antigen-specific antibody responses in mammals [37,38]. Our results indicate that fusing trout C5a to G protein in the recombinant protein vaccine increased both the kinetics and longevity of the antibody response.…”
Section: Discussionmentioning
confidence: 73%
“…Individuals who are able to clear HCV during acute infection have strong cellular immune responses as well as autologous neutralizing antibodies during the early phase of infection (Heim, 2013;Logvinoff et al, 2004;NeumannHaefelin & Thimme, 2013;Pestka et al, 2007;Rehermann, 2009). Whilst other mechanisms exist, the major mechanism of action of neutralizing antibodies is to interfere with or disrupt the interaction between the HCV envelope glycoprotein and the cellular receptor (Burke & Cox, 2010;Di Lorenzo et al, 2011;Edwards et al, 2012;Farci et al, 1994;Giang et al, 2012;Hsu et al, 2003;Johansson et al, 2007;Kaplan et al, 2003;Morin et al, 2012;Neumann-Haefelin & Thimme, 2013;Osburn et al, 2010;Tarr et al, 2012;Troesch et al, 2006;Wahid & Dubuisson, 2013;Wang et al, 2011), such as scavenger receptor class B type I (SR-BI), the tetraspanin protein CD81 and the tightjunction proteins claudin-1 (CLDN1) and occludin (OCLN) (Edwards et al, 2012;Giang et al, 2012;Haberstroh et al, 2008;Johansson et al, 2007;Moradpour et al, 2007;Rice, 2011;Wahid & Dubuisson, 2013;Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As in many other viral infections, the antibody response against HCV plays an important role in protection against initial infection and disease progression (Burke & Cox, 2010;Di Lorenzo et al, 2011;Edwards et al, 2012;Farci et al, 1994;Kaplan et al, 2003;Law et al, 2008;Morin et al, 2012;Neumann-Haefelin & Thimme, 2013;Osburn et al, 2010;Tarr et al, 2012;Troesch et al, 2006;Wahid & Dubuisson, 2013;Wang et al, 2011). Individuals who are able to clear HCV during acute infection have strong cellular immune responses as well as autologous neutralizing antibodies during the early phase of infection (Heim, 2013;Logvinoff et al, 2004;NeumannHaefelin & Thimme, 2013;Pestka et al, 2007;Rehermann, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Also in this current study the platelets count, WBCs, neutrophil, and lymphocyte showed very highly increased significant results (p=0.0001) indicated that haemostatic and immune systems regulate each other with good immunity helping for production of endogenous cytokines including interferon with repair of liver cells, prevent fibrosis, cirrhosis and scar of liver and contribute to spontaneous resolution of HCV virus [46,47].…”
Section: Discussionmentioning
confidence: 85%